Corryocactus brevistylus (K. Schum. ex Vaupel) Britton & Rose (Cactaceae): Antioxidant, Gastroprotective Effects, and Metabolomic Profiling by Ultrahigh-Pressure Liquid Chromatography and Electrospray High Resolution Orbitrap Tandem Mass Spectrometry - Areche, Carlos; Hernandez, Marco; Cano, Teresa; Ticona, Juana; Cortes, Carmen; Simirgiotis, Mario; Caceres, Fátima; Borquez, Jorge; Echeverría, Javier; Sepulveda, Beatriz (Frontiers in Pharmacology, 2020)
Corryocactus brevistylus (Schumann) Britton & Rose (Cactaceae) is popularly known as “sancayo” and produce an edible fruit known as “Sanky” which is consumed in Arequipa-Peru. The purpose of this study was to report the gastroprotective activity and relate this activity to the antioxidant capacity and presence of phenolic compounds for the first time. A metabolomic profiling based on UHPLC/ESI/HR-MS, and the antioxidant activities (DPPH, ABTS and FRAP), ascorbic acid content, total phenolics and flavonoids contents, and the mode of gastroprotective action of the Sanky fruit including the involvement of prostaglandins, nitric oxide, and sulfhydryl compounds is reported. Thirty-eight compounds were detected in the ethanolic extract including twelve organic acids, nine hydroxycinnamic acids, three isoamericanol derivatives, six flavonoids, five fatty acids and two sterols. The results of the biological tests showed that the ethanolic extract had antioxidant capacity and gastroprotective activity on the model of HCl/EtOH-induced gastric lesions in mice (at 10, 25, 50 and 100 mg/kg). The effect elicited by the extract at 50 mg/kg was reversed by indometacin and N-ethylmaleimide but not by NG-nitro-L-arginine methyl ester suggesting that sulfhydryl groups and prostaglandins are involved in the mode of gastroprotective action. In conclusion, our study proves that Corryocactus brevistylus pears have some gastroprotective and antioxidant capacities and consumption is recommended for the presence of several bioactive compounds.